Die sakramentale Struktur der Offenbarung in ökumenischer Auslegung - Lies, Lothar 1940-2008 (2007)
A concept of revelation rooted in communication theory shows that human persons relate to the revelation of the Son of God through the Holy Spirit in either of two manners. The first is through hypostatical union, the second is by way of handing on revelation through sacraments, mission, tradition, scripture, or teaching within the one church. These manners have been seen as opposing each other since the Reformation, but are in reality sacramentally related to one another and only together open up Christ as the foundational sacrament.